The effect of acute gamma radiation onto growth media for mother culture of a Volvariella mushroom - Almugren, K.S.; Sani, S.F. A.; M.S., Jaafar; Azhar, Mohamad; A.S, Siti Shafiqah; Bradley, D.A. * (Elsevier, 2023)
Potato Dextrose Agar (PDA) is a semicrystalline polymer made from amylopectin, agarose, and amylose, used in laboratories for Agar plate culturing for a multitude of fungal strains. The existing pretreatment method for the elimination of pathogenic bacteria, namely steam sterilization, has shown several drawbacks, including high cost, uneven heating due to temperature differentials and an inability to treat specimens volumetrically. These drawbacks are mitigated by gamma irradiation, being carried out in order to improve hygienic quality and germination control, retarding sprouting, also enhancing physical attributes of the food product. Present study investigates the growth and survival of pretreated potato dextrose agar (PDA) substrate with gamma irradiations, for doses ranging from 0 kGy (unirradiated) up to 20 kGy, particularly for Volvariella mushroom cultivation. The relative elemental composition of PDA substrate has been obtained through use of Energy Dispersive X-ray Analysis (EDX), identifying carbohydrate (53.35%), oxygen (45.29%) and 1.36% of mineral trace elements. Gamma irradiation doses to the PDA substrate of 0.5 kGy, 1 kGy and 1.5 kGy have been found to be associated with respective growth rates of 0.93 ± 0.03, 0.94 ± 0.02 and 0.89 ± 0.02 cm/day, the PDA becoming more amorphous and acidic with reduced viscosity at higher doses. The findings of this study could pave the way for a low-cost yet highly effective system for irradiation in mushroom, as well as offering a viable alternative to current conventional sterilizations, well suited to applications in food security.